2006
DOI: 10.7326/0003-4819-145-3-200608010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Hereditary Hemochromatosis: A Systematic Review for the U.S. Preventive Services Task Force

Abstract: Research addressing genetic screening for hereditary hemochromatosis remains insufficient to confidently project the impact of, or estimate the benefit from, widespread or high-risk genetic screening for hereditary hemochromatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 224 publications
2
131
0
3
Order By: Relevance
“…By self-identified race/ethnicity, 44% of the participants were non-Hispanic Caucasians. As previously reported (24), the frequency of homozygosity for the C282Y mutation in this group of non-Hispanic Caucasians was 4.4 per 1000 subjects; consistent with the findings of other screening studies (9,18,(25)(26)(27)(28)(29) had SF below these levels. Eighty-seven other participants with C282Y homozygosity reported they previously were told by a physician that they had hemochromatosis or iron overload, or had been treated by therapeutic phlebotomy, including 39 (45%) women and 48 (55%) men, of median age 56 years (range 25 to 83 years).…”
Section: Study Populationsupporting
confidence: 92%
See 2 more Smart Citations
“…By self-identified race/ethnicity, 44% of the participants were non-Hispanic Caucasians. As previously reported (24), the frequency of homozygosity for the C282Y mutation in this group of non-Hispanic Caucasians was 4.4 per 1000 subjects; consistent with the findings of other screening studies (9,18,(25)(26)(27)(28)(29) had SF below these levels. Eighty-seven other participants with C282Y homozygosity reported they previously were told by a physician that they had hemochromatosis or iron overload, or had been treated by therapeutic phlebotomy, including 39 (45%) women and 48 (55%) men, of median age 56 years (range 25 to 83 years).…”
Section: Study Populationsupporting
confidence: 92%
“…It has been estimated that 10% to 33% of C282Y homozygotes may eventually develop hemochromatosis-associated morbidity (29). The results of the current study indicate that C282Y homozygotes identified by screening for hemochromatosis or iron overload in primary care do not have a significantly increased prevalence of most symptoms and clinical conditions typically associated with hemochromatosis at the time of screening.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The first is BRCA1 testing in breast and ovarian cancer (USPSTF 2005) and the second is screening for HFE mutations to identify individuals at risk for hereditary hemochromatosis in the general population (Whitlock et al 2006). These two topics were chosen about 10 years after the genes for BRCA1 and hemochromatosis were discovered in 1994 and 1996, respectively.…”
Section: So What's Wrong With This Picture?mentioning
confidence: 99%
“…For BRCA1, many years after such tests made their way into practice, the task force found sufficient evidence for a subset of women with the appropriate family history for referral to genetic counseling for decision-making about the possible use of the tests (USPSTF 2005). For HFE testing, the task force found sufficient evidence (among others, the uncertain natural history and low penetrance of HFE mutations) to recommend against screening in the general population (Whitlock et al 2006). A major obstacle to the USPSTF decision-making for both BRCA1 and HFE testing was impeded by the slow accumulation of scientific evidence on clinical utility for testing for these conditions.…”
Section: So What's Wrong With This Picture?mentioning
confidence: 99%